PENGGUNAAN MEDIA WORDWALL DALAM MENINGKATKAN PEMAHAMAN DALAM PEMBELAJARAN IPAS MATERI PANCA INDRA SISWA KELAS IV SEKOLAH DASAR - Sulistia Ningsih; Silvia Dian Suari; Dhiyan Syahirah; Romian Perangin-Angin; Viola Ananta; Destrineli; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to develop students' level of understanding in the context of learning about the five senses of science material through the use of Wordwall media as a tool to help interactive learning. This study was conducted using the Classroom Action Research (CAR) method consisting of two cycles and involving 24 fourth grade students at SDN 165/I Singkawang. Data were obtained by giving tests to participants and collecting documents relevant to the research topic. The findings of this research indicate a significant increase in students' level of understanding after the use of Wordwall media in learning. In the early phase (pre-cycle), the average student score reached 65.58 with a learning success percentage of 45.83%. After the implementation of the first cycle, the completion rate increased to 83.33%. In the second cycle, learning outcomes continued to show improvement with a completion rate of 91.67% and the highest score reaching 100. Wordwall, which is a digital-based learning media, has proven to be effective in supporting students in understanding difficult-to-understand science concepts, while creating a more interactive and enjoyable learning atmosphere. This media provides a varied learning experience through various forms of educational games, thus increasing the enthusiasm and active involvement of students. This research recommends that teachers be more creative in utilizing educational technology for the achievement of optimal learning objectives.